Investigating the electrical percolation threshold of ternary composite films with different compatibility between polymer blends - Xu, Huagen; Qu, Muchao; Yang, Qiancheng; Schubert, Dirk W. (Journal of Polymer Engineering, 2021)
Electrical conductive of polystyrene (PS)/poly(butyl methacrylate) (PBMA)/carbon black (CB) and PS/poly (cyclohexyl methacrylate) (PChMA)/CB ternary composite films with different polymer blend ratios are prepared through solution casting. The percolation thresholds (φc) of all the composite films before and after thermal annealing have been determined through the McLachlan GEM equation. Moreover, the PS/poly (methyl methacrylate) (PMMA)/CB and PS/poly (ethyl methacrylate) (PEMA)/CB films obtained from the same method while only considering conductivity after thermal annealing as well in this work for comparison. Though the CB particles are revealed to be located at only one polymer phase of all four different polymer blends, with compatibility between polymer blends increasing, the ternary composite films show different φc behaviors by changing polymer blend ratios. In PS/PChMA/CB case, the phase separation between PChMA and PS cannot be observed under scanning electron microscope (SEM). After thermal annealing, all the φc of PS/PChMA/CB films with different PS/PChMA ratios almost show a linear behavior instead of the double percolation behavior with PChMA content increasing. Suppose both φc of binary systems (polymer A/filler and polymer B/filler) is determined. In that case, a linear behavior relationship between the φc of the ternary composites (A + B + fillers) with the ratio of two polymers can be revealed when polymer A and B are miscible.
CRIS-Team Scopus Importer:2021-05-21
Keywords: compatibility; electrical conductivity; poly (alkyl methacrylate); polystyrene; ternary composite films